Impact of Critical and Auto Ticket: Analysis for Management and Workers Productivity in using a Ticketing System - Aglibar, Kent Darryl M.; Rodelas, Nelson C. (International Journal of Computing Sciences Research, 2022)
Purpose – Ticketing system is common in Technical Support in Information Technology Industry. At present time, even management is using it. It serves as a way to connect the company and the client, end to end. Support Industry used this also to monitor and log all solutions and processes that come up to resolve the ticket. Client and the resources that will troubleshoot this, use the ticket to have an idea for what is the problem, when the client encountered it, and even the business impact. The researchers conducted research entitled “Impact of Critical and Auto Ticket’s: Analysis for Management and Workers Productivity in using Ticketing System" where it aims to come up with a solution on how we are going to prevent, troubleshoot, and give insight for possible business impact to those everyday issues. This will help the management’s business process to have an analysis to prevent critical issues that will affect the live production as well as give time to their resource to focus on their tasks. Method – Researchers used data collection to gather data from management, support workers, and Service Now’s open-source ticketing system to visualize the ticketing system application. Also, a purposive sampling type of survey has been used to highly represent the data. Results – Critical ticket gives a lot of pressure to the resources as they needed to resolve the incident in accordance with the service level agreement. It affects their productivity to maximize their time to resolve other escalated incidents as they need to focus with critical ones. Instead of maximizing time management and prioritizing employee’s welfare like work and life balance, auto ticket’s affects it because of continuous re-occurring and sometimes needed to be escalated as it will affect the live production. Having knowledge management helps resource to find references on how to deal with the incident. It helps them to execute workaround quickly and think of a way on how to resolve it permanently. Conclusion – It is concluded that critical and auto ticket’s affects the everyday productivity of the worker especially teaching new employees despite ongoing critical incidents. Researchers provided solutions such as knowledge Management and Dashboard to document all the solutions encountered and monitor the SLA’s and incoming tickets. Recommendation – It is recommended to have further research on how critical and auto ticket affects the mental health of resources and its direct impact to businesses. It is also recommended to have a study on how knowledge management work and help resources to identify correct workaround despite of having a lot of troubleshooting guides. Practical Implication – This research benefits data warehousing companies that can be used as a third-party application to connect support team, management, and clients. Management can create a dashboard and identify how their support team provides good quality of service with their response and resolution time. Support team can have a reference to quickly fix escalated incidents and provide ticket number to the client for easily follow up an update.